The effect of islamic education on economic growth (Indonesian and Malaysian studies) - Ika Hajarotin Nisak, Moch Qudsi Fauzy, Sri Herianingrum (Opción, 2019)
This study aims to determine the relationship between the level of Islamic education towards economic growth in Indonesia and Malaysia. The study was conducted by using test Autoregressive Distributed Lag (ARDL) and Granger Causality Test. The results of the study showed that the highest independent variables of education that were completed at the primary, secondary and tertiary levels in the long term did not affect economic growth, but in causalities relations were related to one another. In conclusion, there is a one-way causality relationship between Islamic education variables on economic growth in Malaysia.